Questions for In-Depth Reflection and Improvement of Music Teaching (Appendix to Chapters 30−39) - Kovačič, Bojan (Širjenje obzorij o poučevanju glasbe, 2025)
This chapter presents a series of questions based on the ten chapters of the monograph (Chapters 30−39): Development of Musical Taste, The Influence of Dance on Social Skills, Music and Cross-Curricular Link, The Construction of Musical Instruments, The Importance of Musical Improvisation in Primary School, The Role of the Music Teacher as a Motivator, Musical Performance, Listening to Music, Musical Performance Anxiety, and Musical Improvisation. The questions are divided into four areas (lesson planning, lesson delivery, observation and evaluation, improvement and development) and enable teachers and students to reflect more closely on their own teaching practise.